Some Notes on Stability Conditions - Newman, P. K. (Review of Economic Studies, 1959)
Journal Article Some Notes on Stability Conditions Get access P. K. Newman P. K. Newman Kingston, Jamaica Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 27, Issue 1, October 1959, Pages 1–9, https://doi.org/10.2307/2296045 Published: 01 October 1959